Extracellular pH defense against lactic acid in untrained and trained altitude residents - Böning, D.; Rojas, J.; Serrato, M.; Reyes, O.; Coy, L.; Mora, M. (European Journal of Applied Physiology, 2008)
The assumption that buffering at altitude is deteriorated by bicarbonate (bi) reduction was investigated. Extracellular pH defense against lactic acidosis was estimated from changes (?) in lactic acid ([La]), [HCO3 -], pH and PCO2 in plasma, which equilibrates with interstitial fluid. These quantities were measured in earlobe blood during and after incremental bicycle exercise in 10 untrained (UT) and 11 endurance-trained (TR) highlanders (2,600 m). During exercise the capacity of non-bicarbonate buffers (ß nbi = -?[La] · ?pH-1 - ?[HCO3 -] · ?pH-1) amounted to 40 ± 2 (SEM) and 28 ± 2 mmol l-1 in UT and TR, respectively (P < 0.01). During recovery ß nbi decreased to 20 (UT) and 16 (TR) mmol l-1 (P < 0.001) corresponding to values expected from hemoglobin, dissolved protein and phosphate concentrations related to extracellular fluid (ecf). This was accompanied by a larger decrease of base excess after than during exercise for a given ?[La]. ß bi amounted to 37-41 mmol l-1 being lower than at sea level. The large exercise ß nbi was mainly caused by increasing concentrations of buffers due to temporary shrinking of ecf. Tr has lower ß nbi in spite of an increased Hb mass mainly because of an expanded ecf compared to UT. In highlanders ß nbi is higher than in lowlanders because of larger Hb mass and reduced ecf and counteracts the decrease in [HCO3 -]. The amount of bicarbonate is probably reduced by reduction of the ecf at altitude but this is compensated by lower maximal [La] and more effective hyperventilation resulting in attenuated exercise acidosis at exhaustion.